Responsible consumption and production (RCP) in corporate decision-making models using soft computation - Tseng, Ming Lang (Animo Repository, 2018)
The importance of responsible consumption and production (RCP) in corporate decision-making models using soft computation is discussed. Human and environmental systems interact through the economic system in various ways that have caused many unsustainable issues to arise. Solving these problems is a non-trivial exercise and could be considered one of the world's 'wicked' problems. Wicked problems are complex, intractable, conflicting, and multidimensional problems many times with unforeseen and unintended consequences. It is within this context that the use of soft computation may be a valuable set of tools to handle wicked problems from an RCP perspective. RCP is meant to ensure sustainable consumption and production (SCP) patterns.